(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
Canon law and choral singing: unity and plurality among the people of God. An brief introduction ABSTRACT: Liturgy, music and law seems appartently to be strictly divided dimensions of a religious world. Instead, it is interesting to note how these three different cosmos of religiosity could live together and nurture themself. Even more interesting it is to learn how liturgy law has and music has been used by Catholic and Protestant canon law to shape their different identities through history.